THE IMPACT OF TOURISM CLUSTER FORMATION ON REGIONAL ECONOMIC DEVELOPMENT - Deepan, A.; Fayzullayeva , Sojida; Goyibnazarova , Shahnoza (Effective scientific journals, 2025)
This article examines the impact of tourism cluster formation on regional economic development. Tourism clusters are analyzed as a spatial-economic model that integrates tourism enterprises, infrastructure, supporting industries, and institutional actors within a specific territory. The study explores how tourism clusters contribute to regional economic growth through employment creation, investment attraction, innovation diffusion, and the diversification of local economies. Using a theoretical and analytical approach, the research demonstrates that tourism clusters enhance regional competitiveness and foster sustainable territorial development. The findings highlight the importance of coordinated policy frameworks and institutional support in maximizing the economic benefits of tourism clusters.